Two new species of Esthemopsis C. Felder & R. Felder, 1865 (Lepidoptera: Riodinidae: Symmachiini) from southeastern and northeastern Brazil, with taxonomic comments on Esthemopsis teras (Stichel, 1910) stat. rev. and Esthemopsis pallida Lathy, 1932 stat. nov. - Silva Dias, Fernando Maia; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2014)
Two new species of Esthemopsis C. Felder & R. Felder, 1865 from southeastern and northeastern Brazil are described, Esthemopsis sateri sp. nov. and Esthemopsis diamantina sp. nov., and revised and new combinations are proposed for Esthemopsis teras (Stichel, 1910) stat. rev. and Esthemopsis pallida Lathy, 1932 stat. nov., respectively. Lectotypes are designated for Lepricornis teras Stichel, 1910 and Esthemopsis caerulea pallida Lathy, 1932. The habitus of male and female specimens of the species discussed are illustrated; male head and labial palpus pictures, male and female genitalia illustrations are provided.